PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN MOTOR YAMAHA DI KABUPATEN PADANG PARIAMAN - Jasmalinda Jasmalinda (Jurnal Inovasi Penelitian, 2021)
This study aims to determine the effect of brand image and product quality on consumer purchases of Yamaha motorcycles in Padang Pariaman Regency. The problem that the writer raises in this study is to measure any big influence of brand image (X1) and product quality (X2) on consumer purchasing decisions (Y). In the research the respondents studied were the people of Padang Pariaman Regency as many as 100 respondents. This type of research used in this research is quantitative research with an associative design. The results in this study indicate that the image variable has a positive and significant effect on consumer purchasing decisions. Purchase quality variables have a positive and significant effect on consumer decisions. Brand image and product quality together have a positive and significant effect on consumer purchasing decisions. The result of R² value is 0.405, this means that brand image and product quality are influential with consumer purchasing decisions with a proportion of 40.5%, while the remaining 49.5% applies to other variables not used in this research method. Based on the analysis that has been tested, it can be ignored that the variables of brand image and product quality have a positive and significant effect on consumer purchasing decisions for Yamaha motorbikes in Padang Pariaman Regency.